Surgical Decision Making From Image‐Based Biophysical Modeling of Glioblastoma: Not Ready for Primetime. Issue 5 (May 2017) - Amelot, Aymeric; Deroulers, Christophe; Badoual, Mathilde; Polivka, Marc; Adle‐Biassette, Homa; Houdart, Emmanuel; Carpentier, Antoine F.; Froelich, Sebastien; Mandonnet, Emmanuel
Abstract : BACKGROUND: : Biophysical modeling of glioma is gaining more interest for clinical practice. The most popular model describes aggressivity of tumor cells by two parameters: net proliferation rate (ρ) and propensity to migrate (D). The ratio ρ/D, which can be estimated from a single preoperative magnetic resonance imaging (MRI), characterizes tumor invasiveness profile (high ρ/D: nodular; low ρ/D: diffuse). A recent study reported, from a large series of glioblastoma multiforme (GBM) patients, that gross total resection (GTR) would improve survival only in patients with nodular tumors. OBJECTIVE: : To replicate these results, that is to verify that benefit of GTR would be only observed for nodular tumors. METHODS: : Between 2005 and 2012, we considered 234 GBM patients with pre‐ and postoperative MRI. Stereotactic biopsy (BST) was performed in 109 patients. Extent of resection was assessed on postoperative MRI and classified as GTR or partial resection (PR). Invasiveness ρ/D was estimated from the preoperative tumor volumes on T1‐Gadolinium‐enhanced and fluid‐attenuated inversion recovery sequences. RESULTS: : We demonstrate that patients with diffuse GBM (low ρ/D), as well as more nodular (mid and high ρ/D) GBM, presented significant survival benefit from GTR over PR/BST ( P < .001). CONCLUSION: : Whatever the degree of tumor invasiveness, as estimated from MRI‐driven biophysical modeling, GTR improves survival of GBM patients, compared to PR or BST. This conflicting result should motivate further studies.